1500MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1500MPa-grade nickel-based alloy

By increasing the W element content and optimizing the heat treatment process, the problem of Hastelloy C276 recrystallization at high temperature is solved, and the high tensile strength and elongation of nickel-based alloy is achieved, meeting the material needs of high-temperature and high-field superconducting equipment.

CN119685656APending Publication Date: 2025-03-25INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411589006.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing Hastelloy C276 is prone to recrystallization at high temperatures, resulting in a decrease in tensile strength and cannot meet the development needs of high-temperature and high-field superconducting equipment.

Method used

By increasing the content of W elements, purified smelting and strict control of O and N elements, combined with a heat treatment process of homogenization annealing, solid solution fast cooling and cold deformation, the formation of precipitation phases is avoided and the tensile strength and elongation of nickel-based alloys are improved.

Benefits of technology

The yield strength of the nickel-based alloy is achieved at more than 1400MPa, the tensile strength is above 1550MPa, the elongation is above 3.0%, and the tensile strength is still above 1500MPa, and the elongation is above 7.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685656A_ABST
    Figure CN119685656A_ABST
Patent Text Reader

Abstract

The invention relates to a 1500MPa-grade nickel-based alloy for a second-generation high-temperature superconducting baseband and a preparation method of the 1500MPa-grade nickel-based alloy, and belongs to the technical field of materials. The nickel-based alloy comprises the following chemical components in percentage by weight: 15.0 to 17.0 percent of Cr, 15.0 to 17.0 percent of Mo, 4.5 to 9.5 percent of W, 5.0 to 7.0 percent of Fe, 0.3 to 0.7 percent of Mn, 0.01 to 0.05 percent of Si, 0.1 to 0.2 percent of V, 0.1 to 0.5 percent of Co, 0.1 to 0.2 percent of Al, 0.001 to 0.01 percent of B and Clt, 0.005%, Plt; 0.005%, Slt; 0.002%, Olt; 0.002%, Nlt; 0.002%, and the balance being nickel. On the basis of hastelloy, the strength of a matrix is improved by increasing the W element content, matching an optimized heat treatment process and combining cold deformation; the content of C is controlled, precipitation of carbides is controlled, and it is ensured that the carbides are completely dissolved in a matrix during homogenization treatment; and a pure smelting process is adopted, so that the oxygen content in the alloy is reduced, the inclusion content is controlled, and high purity is ensured. By adopting the component control strategy and the processing preparation and heat treatment process, the nickel-based alloy with the yield strength of 1,300 MPa or above, the tensile strength of 1,500 MPa or above and the ductility of 7.5% or above can be obtained after annealing is conducted for 5 min at the temperature of 900 DEG C, and the requirement of a second-generation high-temperature superconducting high-performance metal base band is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a 1500MPa nickel-based alloy for a second-generation high-temperature superconducting base tape and a preparation method thereof, belonging to the technical field of materials. Background Art

[0002] Since the discovery of the second-generation superconductor of rare earth barium copper oxide (ReBCO, Re is a rare earth element), it has attracted widespread international attention. The second-generation high-temperature superconductor has the advantages of high transition temperature, complete anti-magnetism, high critical current density and high freezing magnetic field, and has been demonstrated in many fields such as electricity, energy and magnets. The most critical superconducting layer in ReBCO is oxide material with poor ductility. Since its thickness is generally less than 4μm, it is also called coating superconductor.

[0003] The realization of ReBCO superconducting properties requires other multifunctional coatings for protection. Usually, the superconducting layer needs to be epitaxially grown on a flexible metal substrate. Therefore, the basis of ReBCO superconductors is the metal substrate. The buffer layer, superconducting layer and protective layer are all built on the metal substrate. Therefore, the comprehensive performance of the metal substrate determines the quality of ReBCO superconducting properties. Ion beam assisted biaxial texture deposition technology (IBAD) has no specific requirements for the orientation and properties of the metal substrate. The ion capacity and beam current can be adjusted independently. The process is flexible and controllable. It is one of the commonly used methods for commercial preparation of ReBCO superconducting layers. IBAD technology has certain requirements for temperature and atmosphere environment during the preparation of the buffer layer, superconducting layer and protective layer. The optimal preparation process parameters of the superconducting layer are 850℃~900℃. Therefore, the metal substrate is required to have good mechanical properties, non-magnetic or weak magnetism, thermal expansion coefficient corresponding to the superconducting layer, good high-temperature structural stability and excellent oxidation resistance. The currently commercially mature Hastelloy C276 has excellent comprehensive properties and is a widely used substrate material for IBAD technology. The tensile strength of Hastelloy C276 after 50% to 90% cold deformation can be above 1300MPa. However, due to the accumulated deformation storage energy of large cold deformation, it is easy to recrystallize when heated to 850℃ to 900℃, resulting in its tensile strength below 1100MPa. It cannot solve the contradiction between large deformation and recrystallization strength of the material, and therefore cannot meet the current development needs of high-temperature and high-field superconductors, thus limiting the further upgrading of high-temperature superconducting equipment.

[0004] With the development of the second generation of high temperature and high field superconductors, higher requirements have been put forward for the operating parameters of key equipment such as high field superconducting magnets prepared therefrom. The metal base tape is required to have a higher recrystallization temperature, to maintain the stability of its structure during the high temperature preparation process of superconductors with large cold deformation, and to have a tensile strength of more than 1500MPa. The tensile strength of the current commercial Hastelloy C276 metal base tape has been reduced to less than 1100MPa due to recrystallization, which cannot meet the current development needs of the second generation of high temperature superconducting metal base tapes. Therefore, in order to upgrade superconducting equipment, it is urgent to develop a new type of nickel-based alloy with a 1500MPa grade for the second generation of high temperature superconductors. Summary of the invention

[0005] The purpose of the present invention is to provide a 1500MPa grade nickel-based alloy for a second-generation high-temperature superconducting base band and a preparation method thereof. On the basis of the traditional Hastelloy C276, by further increasing the W content therein, adopting purification smelting, strictly controlling the O and N content in the alloy, avoiding the formation of large-sized inclusions, controlling the carbon content, adopting a heat treatment process of homogenization annealing and solid solution rapid cooling, avoiding the precipitation of carbides and μ phases, and finally adopting cold deformation to obtain a nickel-based alloy with a yield strength of more than 1400MPa, a tensile strength of more than 1550MPa, and an elongation of more than 3.0%, and after annealing at 900°C for 5min, the yield strength reaches more than 1300MPa, the tensile strength reaches more than 1500MPa, and the elongation reaches more than 7.5%.

[0006] The technical solution of the present invention is:

[0007] A 1500MPa grade nickel-based alloy for a second-generation high-temperature superconducting base tape has the following chemical compositions by weight percentage: Cr: 15.0-17.0%, Mo: 15.0-17.0%, W: 4.5-9.5%, Fe: 5.0-7.0%, Mn: 0.3-0.7%, Si: 0.01-0.05%, V: 0.1-0.2%, Co: 0.1-0.5%, Al: 0.1-0.2%, B: 0.001-0.01%, C<0.005%, P<0.005%, S<0.002%, O<0.002%, N<0.002%, and the balance is nickel.

[0008] The second generation high temperature superconducting base tape uses a 1500MPa grade nickel-based alloy, preferably, C<0.002%, O<0.001%.

[0009] The second generation high temperature superconducting base tape uses a 1500MPa grade nickel-based alloy, preferably, W: 5.5-8.5%.

[0010] The method for preparing the 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape comprises the following steps:

[0011] (1) mixing the chemical components in proportion, and obtaining an ingot through purification smelting and electroslag remelting;

[0012] (2) subjecting the obtained ingot to homogenization annealing treatment at high temperature;

[0013] (3) forging the homogenized annealed ingot in the austenite single phase region;

[0014] (4) The forged alloy ingot is hot rolled: the rolling temperature is 1200°C to 1250°C, the reduction in each rolling pass is controlled to be 20-25%, the total reduction is controlled to be 70-90%, and the hot rolling is followed by water cooling to room temperature;

[0015] (5) Solution heat treatment after hot rolling;

[0016] (6) Cold deformation after solution heat treatment.

[0017] In the method for preparing the 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (2), the temperature of the homogenization annealing treatment is 1250±20°C.

[0018] The method for preparing the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape, in step (3), the forging process is: forging temperature 1220-1250°C, forging ratio above 6.0, and air cooling to room temperature after forging.

[0019] In the method for preparing the 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (5), the solution heat treatment process is: keeping at 1160°C to 1200°C for 2 to 4 hours and then quenching with water to room temperature.

[0020] In the method for preparing the 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape, in step (6), the cold deformation process is: cold deformation is performed at room temperature, and the cold deformation amount is 50-90%.

[0021] The preparation method of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape, the yield strength of the nickel-based alloy after cold deformation reaches more than 1400MPa, the tensile strength reaches more than 1550MPa, and the elongation reaches more than 3.0%; after annealing at 900°C for 5 minutes, the yield strength reaches more than 1300MPa, the tensile strength reaches more than 1500MPa, and the elongation reaches more than 7.5%.

[0022] The content range of the main elements in the present invention is described as follows:

[0023] Cr: Chromium is an important element of Hastelloy alloy and the primary element that determines the corrosion resistance of Hastelloy alloy. This is because chromium improves the corrosion resistance of the alloy itself and makes it easy for the material to form a chromium oxide layer on it. However, when the Cr content is less than 15wt%, the minimum corrosion resistance required by the alloy cannot be obtained. On the other hand, when the Cr content exceeds 17wt%, chromium-rich intermetallic compounds are easily precipitated, thus forming a chromium-poor zone around the intermetallic compounds, which not only causes the material's hot working properties and mechanical properties to be impaired, but also deteriorates the material's oxidation corrosion resistance. Therefore, in order to ensure that the material has excellent corrosion resistance to most corrosive media in both oxidation and reduction states, the chromium content in the alloy of the present invention is controlled to be: 15.0-17.0wt%.

[0024] Mo: Molybdenum, like chromium, is a corrosion-resistant element with an ability comparable to that of chromium. The interaction between molybdenum and the corrosive medium will prompt the formation of a dense and uniform passivation film on the surface, reduce the possibility of corrosion of the alloy, and significantly improve its corrosion resistance. In addition, Mo can enhance the solid solution strengthening effect of nickel-based alloys, improve the strength and service performance of the alloy. However, excessive Mo content will suffer varying degrees of oxidation during hot working, deteriorating the processing and use performance of the alloy. Therefore, molybdenum with the effect of improving corrosion resistance can be added within the range that does not damage other properties of the material, such as corrosion resistance, hot workability, and weldability. Therefore, the molybdenum content in the alloy of the present invention is controlled to be: 15.0~17.0wt%.

[0025] W: The role of tungsten is similar to that of Mo, and it mainly plays a role in solid solution strengthening in the alloy system. Since the atomic radius of W is larger than that of Mo, the solid solution strengthening effect is greater than that of Mo, and due to the high melting point of W, appropriately increasing its content will increase the recrystallization temperature of the alloy after cold working to a certain extent, which is also one of the keys of the present invention. However, too high W will cause the alloy to form a relatively stable nickel-rich and molybdenum-rich μ phase, which cannot be completely eliminated even if the solid solution temperature is maintained for a long time at a very high solid solution temperature. Therefore, in order to avoid the influence of precipitation on superconducting properties, the content of W needs to be strictly controlled. Therefore, the content of W in the alloy of the present invention is controlled to be: 4.5-9.5wt%, and further optimized to 5.5-8.5wt%.

[0026] Fe: The addition of iron is mainly to control the cost of the alloy system, because nickel and iron can be infinitely soluble in each other. The addition of Fe replaces the atomic position of Ni, causing the lattice to be distorted, so it can have a certain effect of solid solution strengthening. Too much Fe will form Laves phase with Mo and W in the matrix, thereby deteriorating the performance of the material. Therefore, the content of iron in the alloy of the present invention is controlled to be: 5.0-7.0wt%.

[0027] Mn: Manganese can enhance the strength and toughness of the alloy through the solid solution strengthening mechanism. Mn replaces the nickel atoms in it, causing distortion, thereby hindering the movement of dislocations and increasing the yield and tensile strength of the material. At the same time, it can significantly reduce the martensite formation temperature M of the alloy. S point, ensuring the stability of the alloy austenite structure. When the Mn content is added too high, it is easy to form MnS inclusions with S in the alloy, and the increase in the volume fraction of the inclusions reduces the impact toughness of the alloy. Therefore, the manganese content in the alloy of the present invention is controlled to be: 0.3-0.7wt%.

[0028] Si: The silicon element plays several key roles: First, as a deoxidizer, silicon helps remove oxygen from the smelting liquid and reacts with oxygen to form silicon oxide, thereby improving the purity and overall quality of the alloy. Second, silicon enhances the strength and hardness of the alloy through a solid solution strengthening mechanism. However, the silicon content needs to be controlled because too high a silicon content may affect the welding performance of the alloy. Therefore, the silicon content in the present invention is controlled to be: 0.01 to 0.05wt%.

[0029] V: Vanadium is a strong carbide-forming element, which easily forms precipitation phases with carbon and nitrogen in the alloy and pins dislocations. V can fix carbon elements and prevent alloying elements such as Cr from diffusing from the matrix into carbides to cause ripening, thereby improving the mechanical strength of the alloy. When the vanadium content is low, it is not easy to fully form fine carbides and cannot play the role of pinning dislocations, while when the content is high, the alloy becomes brittle. Therefore, the vanadium content in the alloy of the present invention is controlled to be: 0.1-0.2wt%.

[0030] Co: Cobalt is basically completely dissolved in the matrix, plays a role in solid solution strengthening, and does not form carbides. It forms a synergistic effect with Mo to promote the precipitation of precipitation phases. Cobalt can inhibit the recovery of dislocation substructures in the microstructure, provide more nucleation sites for subsequent precipitation phases, and promote precipitation strengthening. Therefore, according to the balancing effect of cobalt on the alloy and its influence on the precipitation effect of the precipitation phase, the content of cobalt in the alloy of the present invention is controlled to be: 0.1-0.5wt%.

[0031] Al: Aluminum is an element that forms the γ′ strengthening phase of the intermetallic compound and is an important element for improving the strength of the alloy. At the same time, the Al content is also an important indicator of the material's resistance to high-temperature oxidation. There is a short high-temperature process in the preparation of the ReBCO superconducting layer, so a higher requirement is placed on the oxidation resistance of the material of the present invention. Therefore, the Al content of the alloy of the present invention is optimized and controlled to be: 0.1-0.2wt%.

[0032] B: A trace amount of boron can greatly improve the mechanical properties of the alloy. Boron is a basic grain boundary strengthening element in polycrystalline high-temperature alloys. Boron can segregate at the grain boundary to increase the grain boundary bonding force, improve the fracture strength, consume or reduce the agglomerate precipitation phase of the grain boundary, reduce the content of harmful elements such as S on the grain boundary through position competition, and improve the slip and dislocation climb on the grain boundary to prevent the generation of cracks. Moreover, it can form borides with metals to strengthen the grain boundary. Therefore, the boron content in the alloy of the present invention is controlled to be 0.001-0.01wt%, and further optimized to: 0.001-0.003wt%.

[0033] C: Carbon easily forms M with elements such as Cr in alloys 23 C6 carbides, especially during the slow cooling process after solutionization, will precipitate. Although carbides precipitate at the original austenite grain boundary interface, they can pin dislocations and hinder the movement of the interface, play a role in precipitation strengthening, and effectively improve the strength of the material. However, the precipitation of these precipitated phases of carbides will affect the superconducting properties of the second-generation superconductors, and the carbon content in the alloy needs to be strictly controlled. Therefore, the ultra-low carbon component design idea is adopted, and the C content in the alloy of the present invention is optimized and controlled to: C < 0.005wt%, and further optimized to C < 0.002wt%.

[0034] S, P: In the production of nickel-based alloys, phosphorus and sulfur are generally regarded as harmful impurities because they can significantly reduce the overall performance of the alloy. P will promote the segregation of W and Mo to form Laves phase, thereby increasing the cold brittleness of the alloy, reducing the cohesion of the grain boundaries, thereby reducing the toughness and plasticity of the material, and will also affect the welding performance, causing the welded joints to be prone to cracks. On the other hand, sulfur will increase the tendency of the material to be hot brittle, especially during processing. At the same time, excessive sulfur will also affect the mechanical processing quality of the material and reduce the strength and toughness of the material. Therefore, the content of sulfur and phosphorus in the alloy of the present invention is extremely strictly controlled: S<0.002wt%, P<0.005wt%.

[0035] O: Oxygen is the main element that produces oxide inclusions in the alloy. Therefore, in order to reduce the inclusions in the alloy and ensure the purity of the material, the oxygen content must be reduced as much as possible. When the oxygen content in the material exceeds a certain limit, especially when the material of the present invention contains a certain amount of Al, continuous brittle oxide inclusions will be formed in the alloy, which will form stress concentration during the processing of the thin strip, resulting in the occurrence of strip breaking accidents. Therefore, the oxygen content in the alloy of the present invention is strictly controlled: O<0.002wt%, further optimized to: O<0.001wt%.

[0036] N: Nitrogen is a strong austenite-forming element, which expands the austenite phase area, shrinks the ferrite phase area, and can inhibit the formation of high-temperature ferrite. Although nitrogen can increase the cold working hardening rate and improve the strength index of the alloy after cold working, since a certain amount of B element is added in the present invention, in order to avoid the formation of BN inclusions, it is necessary to strictly control the N element content in the material of the present invention. Therefore, the nitrogen content in the alloy of the present invention is extremely strictly controlled: N<0.002wt%.

[0037] The innovative design ideas of the present invention are as follows:

[0038] 1) Innovative alloy composition design: Based on the Ni-Cr-Mo Hastelloy alloy, the present invention increases the W element therein and optimizes the subsequent processing and preparation process. While no precipitated phase is precipitated, W is completely dissolved into the nickel-based alloy matrix, and the solid solution strengthening effect of W in the Ni-Cr-Mo Hastelloy alloy is fully exerted. After cold deformation with a deformation amount of 50% to 90%, the tensile strength of the material of the present invention is above 1550MPa, and after annealing at 900°C for 5 minutes, the tensile strength of the material of the present invention is still as high as 1500MPa, which is higher than the currently commercial Hastelloy C276.

[0039] 2) Matching of processing and heat treatment system: The nickel-based alloy of the present invention contains 15-17wt% of Cr and Mo elements. The design of high W content will make the μ phase and P phase in Ni-Cr-Mo Hastelloy more stable. As a superconducting baseband material, the precipitated phase therein will affect its superconducting performance to a certain extent. Therefore, how to ensure the grain size of the material while there is no precipitated phase in the nickel-based alloy matrix is ​​a key. The material of the present invention ensures that the material is tempered at a higher temperature during the forging process to reduce the number of times of the material, thereby ensuring the grain size of the material. At the same time, a rapid cooling method after solid solution is adopted to avoid the precipitation of the precipitated phase. The material adopts a matching between special processing and solid solution heat treatment system to ensure the realization of the design concept of high W content of the material.

[0040] 3) Purification smelting technology: Purification smelting technology is used to strictly control the content of harmful elements such as P, S, O and N in the alloy that are easy to form inclusions. The O content is controlled below 10ppm, and the P and S contents are controlled below 50 and 20ppm respectively, reducing the formation of inclusions in the alloy and laying a good foundation for the subsequent preparation of 20-50μm superconducting substrates.

[0041] 4) Final cold deformation process control: Break the tradition of regulating the heat treatment organization of the material as the final treatment. By controlling the cold deformation amount within 50% to 90%, the grains are further refined, a large number of dislocations are introduced into the nickel-based alloy matrix, and the W element is used to strengthen the solid solution and increase the recrystallization temperature of the material to ensure the stability of the material performance during the preparation of the ReBCO superconducting layer, laying a material foundation for the realization of high-temperature and high-field superconductivity.

[0042] The advantages and beneficial effects of the present invention are:

[0043] 1. Based on the traditional Ni-Cr-Mo Hastelloy C276 material, the present invention optimizes the content of the key alloy element W to 5.5-8.5wt%, which is 3wt% higher than the W content in the current commercial Hastelloy C276. Through the optimization and matching of the subsequent preparation and heat treatment systems, the problem of excessive W in the material promoting the stability of the precipitation phase is solved, and W is completely dissolved in the nickel-based alloy matrix, thereby fully exerting the solid solution strengthening effect of W in the material, and further improving the recrystallization temperature of the material after cold deformation.

[0044] 2. The present invention adopts purification smelting technology to greatly reduce the oxygen content in the material of the present invention. On this basis, the content of P, S and N elements in the material is further reduced to ensure that the inclusion content of the material of the present invention is at an extremely low level, further improve its purity, and stably prepare superconducting base strips with a thickness of 20 to 50 μm. A nickel-based alloy with high purity and high strength and toughness is obtained, which meets the material requirements of high-temperature and high-field superconducting equipment.

[0045] 3. The present invention provides a 1500MPa nickel-based alloy for the second-generation high-temperature superconducting baseband and a key preparation process. By adopting the technical solution provided by the present invention, a high-purity and high-strength nickel-based high-temperature alloy can be stably obtained. The material of the present invention can better support the rapid development of my country's high-temperature and high-field superconducting industry and promote the upgrading of industry equipment. At the same time, it also provides a new idea for the development and application of high-strength nickel-based alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a schematic diagram of the metallographic structure of Example 1 after forging.

[0047] Figure 2 Schematic diagram of the metallographic structure after solid solution of Example 2.

[0048] Figure 3 Schematic diagram of the metallographic structure of Comparative Example 1 after forging.

[0049] Figure 4 Schematic diagram of the electron probe microanalysis (EPMA) element distribution after solid solution of Comparative Example 2. Among them, (a) is the C element, (b) is the W element, (c) is the Ni element, and (d) is the Mo element.

[0050] Figure 5 Schematic diagram of the electron probe microanalysis (EPMA) element distribution after solid solution of Comparative Example 3. Among them, (a) is the C element, (b) is the N element, (c) is the W element, and (d) is the B element. DETAILED DESCRIPTION

[0051] In the specific implementation process, the present invention further optimizes the W content to 5.5-8.5wt% on the basis of the traditional material Hastelloy C276, matches the optimized hot working and heat treatment system, realizes the complete solid solution of W in the nickel-based alloy matrix, solves the problem that too high W in the material brings more stable TCP phases such as μ phase and P phase, fully exerts the solid solution strengthening effect of W in the nickel-based alloy, and further improves the recrystallization temperature of the nickel-based alloy after cold deformation. In addition, by controlling the C content, the precipitation of carbides is controlled to ensure that they are completely dissolved into the matrix during homogenization treatment; a pure smelting process is adopted to reduce the oxygen content in the alloy, control the inclusion content, and ensure high purity. After cold deformation, the yield strength of the material of the present invention reaches more than 1450MPa, the tensile strength reaches more than 1600MPa, and the elongation reaches 4.0%. Moreover, after annealing at 900℃ for 5min, the yield strength of the material of the present invention still reaches more than 1300MPa, the tensile strength reaches more than 1500MPa, and the elongation reaches more than 7.5%.

[0052] The following examples and drawings will further illustrate the present invention, but are not intended to limit the present invention. The nickel-based alloys in the examples and the alloys in the comparative examples were processed into standard plate-shaped tensile specimens after smelting and heat treatment to test the mechanical properties.

[0053] The preparation process of the 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape of the present invention is: batching → smelting → casting → homogenization → forging and hot working → heat treatment → cold working. Examples 1 to 5 are all prepared by the following method, and the specific steps are as follows:

[0054] (1) mixing the chemical components in proportion, and obtaining an ingot through smelting and electroslag remelting;

[0055] (2) The temperature of the homogenization annealing treatment is 1250±20°C (1230°C, 1250°C, 1260°C, 1244°C, and 1266°C in Examples 1 to 5, respectively), and the temperature is kept for 20h to 30h (20h, 25h, 30h, 22h, and 28h in Examples 1 to 5, respectively), and then air-cooled;

[0056] (3) forging the ingot after homogenization annealing in the austenite single phase region: the forging temperature is 1220° C. to 1250° C. (Examples 1 to 5 are 1220° C., 1250° C., 1235° C., 1226° C., and 1244° C., respectively), the forging ratio is above 6 (Examples 1 to 5 are 6.0, 12.0, 10.5, 9.5, and 11.0, respectively), and air cooling to room temperature after forging;

[0057] (4) The forged alloy ingot is hot rolled: the hot rolling temperature is 1200°C to 1250°C (1200°C, 1250°C, 1225°C, 1213°C, and 1235°C in Examples 1 to 5, respectively), the reduction in each rolling pass is controlled to be 20% to 25% (20%, 25%, 22%, 21%, and 24% in Examples 1 to 5, respectively), and the total reduction is controlled to be 80% to 90% (80%, 90%, 85%, 82%, and 88% in Examples 1 to 5, respectively), and the hot rolling is followed by water cooling to room temperature;

[0058] (5) after hot rolling, solution heat treatment is performed: solution temperature is 1160°C to 1200°C (1161°C, 1195°C, 1185°C, 1175°C, and 1190°C in Examples 1 to 5, respectively), holding time is 2h to 4h (2.0h, 4h, 3h, 2.5h, and 3.5h in Examples 1 to 5, respectively), and then water-cooled to room temperature;

[0059] (6) Cold deformation at room temperature after solution heat treatment: the cold deformation amount is 50-90% (Examples 1-5 are 50%, 90%, 70%, 60%, and 80%, respectively).

[0060] The present invention is further described in detail below through the accompanying drawings and embodiments.

[0061] Example 1

[0062] In this embodiment, the chemical composition of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr: 16.11%, Mo: 15.93%, W: 7.05%, Fe: 6.13%, Mn: 0.51%, Si: 0.03%, V: 0.15%, Co: 0.30%, Al: 0.14%, B: 15ppm, C: 12ppm, P: 24ppm, S: 18ppm, O: 4ppm, N: 13ppm, and the balance is nickel.

[0063] Example 2

[0064] In this embodiment, the chemical composition of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr: 15.12%, Mo: 16.97%, W: 8.49%, Fe: 5.11%, Mn: 0.45%, Si: 0.034%, V: 0.14%, Co: 0.31%, Al: 0.12%, B: 12ppm, C: 11ppm, P: 48ppm, S: 12ppm, O: 3ppm, N: 17ppm, and the balance is nickel.

[0065] Example 3

[0066] In this embodiment, the chemical composition of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr: 16.98%, Mo: 15.21%, W: 5.51%, Fe: 6.85%, Mn: 0.68%, Si: 0.011%, V: 0.11%, Co: 0.12%, Al: 0.11%, B: 11ppm, C: 14ppm, P: 27ppm, S: 16ppm, O: 8ppm, N: 14ppm, and the balance is nickel.

[0067] Example 4

[0068] In this embodiment, the chemical composition of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr: 15.51%, Mo: 16.51%, W: 6.31%, Fe: 6.52%, Mn: 0.31%, Si: 0.048%, V: 0.19%, Co: 0.49%, Al: 0.18%, B: 29ppm, C: 17ppm, P: 31ppm, S: 8ppm, O: 4ppm, N: 10ppm, and the balance is nickel.

[0069] Example 5

[0070] In this embodiment, the chemical composition of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting base tape is, by weight percentage, Cr: 16.49%, Mo: 15.48%, W: 7.76%, Fe: 5.51%, Mn: 0.62%, Si: 0.046%, V: 0.15%, Co: 0.21%, Al: 0.12%, B: 22ppm, C: 5ppm, P: 21ppm, S: 6ppm, O: 3ppm, N: 12ppm, and the balance is nickel.

[0071] Comparative Example 1

[0072] In this comparative example, the W content in the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate is 4.05wt% by weight, and the other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 1.

[0073] Comparative Example 2

[0074] In this comparative example, the W content in the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate is 10.0wt% by weight, and the other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 2.

[0075] Comparative Example 3

[0076] In this comparative example, the N content of the 1500MPa grade nickel-based alloy for the second-generation high-temperature superconducting substrate is 35ppm by weight, and the other chemical compositions, homogenization treatment, forging process, hot rolling process, solution treatment and cold working process are exactly the same as those in Example 3.

[0077] Table 1 Mechanical properties of the plates after cold rolling of the embodiments and comparative examples

[0078] Serial number <![CDATA[Yield strength Rp 0.2 , MPa]]> Tensile strength Rm, MPa Elongation A, % Example 1 1476 1605 4.5 Example 2 1525 1627 3.5 Example 3 1424 1581 5.5 Example 4 1451 1596 5.1 Example 5 1493 1617 4.2 Comparative Example 1 1342 1427 8.5 Comparative Example 2 1427 1545 2.1 Comparative Example 3 1386 1476 6.5

[0079] As can be seen from Table 1, the present invention, based on the traditional material Hastelloy C276, innovatively adds an optimized content of W element, matches the optimized hot working process and heat treatment system, ensures that the added W is completely dissolved into the nickel-based alloy matrix, and through a cold rolling reduction of 50-90% deformation, a nickel-based alloy with excellent mechanical properties can be obtained, with a yield strength of more than 1424MPa, a tensile strength of more than 1581MPa, and an elongation of more than 3.5%. The W content in Comparative Example 1 is controlled within the component control standard of Hastelloy C276 of 3.0-4.5wt%. Compared with Example 1, it is found that the yield strength of commercial Hastelloy C276 reaches 1342MPa and the tensile strength reaches 1427MPa, which are lower than the performance indicators of the material of the present invention. The W content in Comparative Example 2 reaches 10wt%, which is not within the W component control range of the present invention. Since W is not completely dissolved into the nickel-based alloy matrix, and since there are large-sized undissolved W-rich phases (such as) in the nickel-based alloy matrix, the W content in the nickel-based alloy matrix is ​​10wt%. Figure 4 As shown in Figure 2, the mechanical properties are relatively low, especially the elongation is only 2.1%. The N content in Comparative Example 3 is not controlled within the composition requirements of the present invention, resulting in the presence of BN in the nickel-based alloy matrix (as shown in Figure 2). Figure 5 As shown in the figure, BN acts as a heterogeneous nucleation site, resulting in the incomplete solid solution of the W-rich phase in the Ni-based alloy matrix, resulting in lower mechanical properties.

[0080] Table 2 Mechanical properties of cold-rolled plates of embodiments and comparative examples after annealing at 900°C for 5 min and air cooling

[0081] Serial number <![CDATA[Yield strength Rp 0.2 , MPa]]> Tensile strength Rm, MPa Elongation A, % Example 1 1395 1542 8.5 Example 2 1430 1551 7.8 Example 3 1352 1528 9.6 Example 4 1375 1536 9.1 Example 5 1420 1549 8.2 Comparative Example 1 942 1105 25.2 Comparative Example 2 1342 1487 5.1 Comparative Example 3 1267 1382 12.0

[0082] As can be seen from Table 2, after annealing at 900°C for 5min, the yield strength and tensile strength of the material of the present invention are reduced to a certain extent, but the elongation is greatly improved, wherein the yield strength is above 1352MPa, the tensile strength is above 1528MPa, and the elongation is above 7.8%. This is because W is completely dissolved into the nickel-based alloy matrix, which increases the recrystallization temperature of the nickel-based alloy matrix. After 900°C insulation for 5min, the cold-rolled nickel-based alloy matrix does not recrystallize, and only a certain degree of dynamic recovery occurs, so the tensile strength of the material of the present invention remains above 1500MPa. However, the W content in Comparative Example 1 is relatively low, and the material undergoes recrystallization, and its yield strength reaches 942MPa, and its tensile strength is only 1105MPa, and the strength index does not meet the index requirements of the material of the present invention. In Comparative Example 2, since W is not completely dissolved, its tensile strength is only 1487MPa, which still does not meet the index requirements of the material of the present invention. Similarly, the strength index of Comparative Example 3 does not reach the required range.

[0083] like Figure 1 As shown, the metallographic structure of Example 1 after air cooling at 1220°C large deformation forging. It can be seen from the figure that after one hot working, the dendrites of the original cast structure are broken, and the homogenization and insulation stage before forging promote the W in the nickel-based alloy matrix to dissolve back into the nickel-based alloy matrix. After forging cooling, the material of the present invention does not undergo recrystallization.

[0084] like Figure 2 As shown, the metallographic structure of Example 2 after solution treatment at 1200°C for 4 hours. It can be seen from the figure that after homogenization treatment, large deformation forging, hot rolling above 1200°C and solution treatment, the W in Example 2 is completely dissolved into the matrix, and there is no precipitate phase on the grain boundary.

[0085] like Figure 3 As shown, the metallographic structure of Comparative Example 1 after air cooling at 1220°C large deformation forging is partially recrystallized, and the recrystallization rate reaches 16.0%. This is because the W content is low and is not within the composition control range of the present invention. Therefore, under large deformation storage energy, Comparative Example 1 undergoes partial recrystallization.

[0086] like Figure 4As shown, Comparative Example 2 is a schematic diagram of EPMA element distribution after solution treatment at 1200°C for 4 hours. It can be seen from the figure that although it is water-cooled to room temperature after being kept at 1200°C for 4 hours, large particles of undissolved W-rich phases are still present in the grain boundaries and in the grains of the nickel-based alloy matrix. Since the W content in Comparative Example 2 is as high as 10.0wt%, which is higher than the control requirement of the present invention for the W element composition, although the same processing and heat treatment process as Example 2 is used, undissolved W-rich phases are still present in the nickel-based alloy matrix.

[0087] like Figure 5 As shown, Comparative Example 3 is a schematic diagram of EPMA element distribution after solution treatment at 1180°C for 3 hours. It can be seen from the figure that since the N content is higher than the requirement of the present invention for controlling its composition, a W-rich phase with BN as the core exists on the grain boundary, resulting in lower mechanical properties of Comparative Example 3.

[0088] The mechanical property test results of the above-mentioned embodiments 1 to 5 show that the second-generation 1500MPa grade nickel-based alloy for high-temperature superconducting of the present invention is based on the commercial Hastelloy C276, and 5.5 to 8.5wt% of W is optimized, and the subsequent optimized homogenization treatment, hot working, heat treatment process and cold working are matched. After cold rolling, the yield strength is finally obtained to reach more than 1424MPa, the tensile strength is more than 1581MPa, and the elongation is more than 3.5%. Moreover, after annealing at 900℃ for 5min, the yield strength of the material is as high as more than 1352MPa, the tensile strength is as high as more than 1528MPa, and the elongation is as high as more than 7.8%. The second-generation 1500MPa grade nickel-based alloy for high-temperature superconducting is obtained. Thus, the best combination of strength and toughness of the nickel-based alloy is obtained, which meets the needs of high-performance metal substrates for the second-generation high-temperature superconducting.

[0089] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A 1500MPa grade nickel-based alloy for second generation high temperature superconducting base tape, characterized in that: In terms of weight percentage, its chemical composition is: Cr: 15.0-17.0%, Mo: 15.0-17.0%, W: 4.5-9.5%, Fe: 5.0-7.0%, Mn: 0.3-0.7%, Si: 0.01-0.05%, V: 0.1-0.2%, Co: 0.1-0.5%, Al: 0.1-0.2%, B: 0.001-0.01%, C<0.005%, P<0.005%, S<0.002%, O<0.002%, N<0.002%, and the balance is nickel.

2. The 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape according to claim 1, characterized in that: Preferably, C<0.002%, O<0.001%.

3. The 1500MPa grade nickel-based alloy for the second generation high temperature superconducting base tape according to claim 1, characterized in that: Preferably, W: 5.5-8.5%.

4. A method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate as claimed in any one of claims 1 to 3, characterized in that: The steps include: (1) mixing the chemical components in proportion, and obtaining an ingot through purification smelting and electroslag remelting; (2) subjecting the obtained ingot to homogenization annealing treatment at high temperature; (3) forging the homogenized annealed ingot in the austenite single phase region; (4) The forged alloy ingot is hot rolled: the rolling temperature is 1200°C to 1250°C, the reduction in each rolling pass is controlled to be 20-25%, the total reduction is controlled to be 70-90%, and the hot rolling is followed by water cooling to room temperature; (5) Solution heat treatment after hot rolling; (6) Cold deformation after solution heat treatment.

5. The method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 4, characterized in that: In step (2), the temperature of the homogenization annealing treatment is 1250±20°C.

6. The method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 4, characterized in that: In step (3), the forging process is as follows: forging temperature is 1220-1250° C., forging ratio is above 6.0, and air cooling is performed to room temperature after forging.

7. The method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 4, characterized in that: In step (5), the solution heat treatment process is: keeping at 1160°C to 1200°C for 2 to 4 hours and then quenching with water to room temperature.

8. The method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 4, characterized in that: In step (6), the cold deformation process is: cold deformation is performed at room temperature, and the cold deformation amount is 50 to 90%.

9. The method for preparing a 1500MPa grade nickel-based alloy for a second generation high temperature superconducting substrate according to claim 4, characterized in that: The yield strength of the nickel-based alloy after cold deformation reaches more than 1400MPa, the tensile strength reaches more than 1550MPa, and the elongation reaches more than 3.0%; after annealing at 900℃ for 5min, the yield strength reaches more than 1300MPa, the tensile strength reaches more than 1500MPa, and the elongation reaches more than 7.5%.

Citation Information

Cited By

  • 1300MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1300MPa-grade nickel-based alloy

    CN119753431A

  • 1400 MPa-grade nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1400 MPa-grade nickel-based alloy

    CN119899958A

  • 1200MPa-grade low-cost nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1200MPa-grade low-cost nickel-based alloy

    CN120138435A

  • 1600MPa-grade high-strength nickel-based alloy for second-generation high-temperature superconducting baseband and preparation method of 1600MPa-grade high-strength nickel-based alloy

    CN120249742A

  • High-plasticity and high-strength-ductility nickel-based alloy for second-generation high-temperature superconducting base band and preparation method of high-plasticity and high-strength-ductility nickel-based alloy

    CN120249743A